Retrospection methods in translator training and translation research - Gyde Hansen (JoSTrans: The Journal of Specialised Translation)
This article presents the results of the Copenhagen Retrospection Project which was carried out at CBS in 2004 in connection with research in translation processes. It is a systematic comparison of several methods for introspection, the Integrated Problem and Decision Report (IPDR) by Gile (2004), Retrospection with Replay with Translog (R+Rp) and Retrospection with Replay combined with cognitive clarification via an immediate dialogue(ID) between the subject and the observer (R+Rp+ID). The methods were tested and compared in terms of their applicability, their influence on the number of problems and decisions mentioned by the subjects, the amount of information each of them provides, their long-term effect on trainees, as well as their general value for translator training and translation research. The most important results are that they all contribute to raising awareness of the translation process and that they - though they differ in many respects, especially as to source consultation - are suited to be used complementarily, both together and combined with other methods.